DARI SWISS KE IRAN: “DALAM UPAYA MENDUKUNG GERAKAN SOSIAL PEMENUHAN HAM BAGI PEREMPUAN IRAN MELALUI NON GOVERNMENT ORGANIZATION SWISS” - Mutiara Agustin Br. Haloho (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The struggle for equal rights for women existed before the Islamic Revolution. To ensure that there are gender interests which are important in fulfilling the Sustainable Development Goals (SDGs) in social life.This study is seek to answer the actions of Iranian women as a society that has the same position and status and is able to contribute in the political field and women's participation to be able to participate in the political field and which is supported by Swiss women's institutions to elevate the role of women in Iran after the revolution through Non-Government Organization.This study uses the theory of Liberal Feminism which is one of the theories of International Relations in supporting the fulfillment of human rights for women. The results of the study show that the presence of Switzerland encourages the fulfillment of human rights for Iranian women. Switzerland has been present in Iran for 40 years and is a country of communication between the US and Iran together by supporting the fulfillment of Iranian women's human rights through NGOs and the existence of CEDAW as a convention on women's human rights, there is still a gap in human rights between men and women in Iran.